Rare case of intrahepatic splenosis masquerading as malignancy. Issue 7 (14th March 2022) - Anderson, Max; Connor, Saxon; Hamilton, Steve; Hore, Todd; Sakowska, Magdalena
Summary: A 54‐year‐old man presented with abdominal pain and a history of post‐traumatic splenectomy 33 years prior, imaging revealed an incidental hepatic mass.